The rate of telomere loss is related to maximum lifespan in birds. (5th March 2018) - Tricola, Gianna M.; Simons, Mirre J. P.; Atema, Els; Boughton, Raoul K.; Brown, J. L.; Dearborn, Donald C.; Divoky, G.; Eimes, John A.; Huntington, Charles E.; Kitaysky, Alexander S.; Juola, Frans A.; Lank, David B.; et al.
Abstract : Telomeres are highly conserved regions of DNA that protect the ends of linear chromosomes. The loss of telomeres can signal an irreversible change to a cell's state, including cellular senescence. Senescent cells no longer divide and can damage nearby healthy cells, thus potentially placing them at the crossroads of cancer and ageing. While the epidemiology, cellular and molecular biology of telomeres are well studied, a newer field exploring telomere biology in the context of ecology and evolution is just emerging. With work to date focusing on how telomere shortening relates to individual mortality, less is known about how telomeres relate to ageing rates across species. Here, we investigated telomere length in cross-sectional samples from 19 bird species to determine how rates of telomere loss relate to interspecific variation in maximum lifespan. We found that bird species with longer lifespans lose fewer telomeric repeats each year compared with species with shorter lifespans. In addition, phylogenetic analysis revealed that the rate of telomere loss is evolutionarily conserved within bird families. This suggests that the physiological causes of telomere shortening, or the ability to maintain telomeres, are features that may be responsible for, or co-evolved with, different lifespans observed across species. This article is part of the theme issue 'Understanding diversity in telomere dynamics'.